A terapia comunitária como estratégia de intervenção para o empoderamento de usuários de CAPS em processo de alta - Silva, Priscilla Maria de Castro (2016)
Introduction: The Integrated Community Therapy (ICT) is an environment for speaking, listening and creating bonds which is carried out according to precise rules which allow for confronting strategies towards daily uneasiness to be come up with in view of a situationproblem. This study aims at analyzing the effect of ICT as an advanced therapy for psychosocial intervention, assessing its contribution for improving self-esteem and bonds in users of a Psychosocial Attention Center (CAPS), resulting in the strengthening of autonomy and empowering which are both necessary after discharge. The fieldwork followed the ethical precepts (CAAE 44866015.0.0000.5188) and took place at a CAPS in the city of Campina Grande, PB, Brazil, and it was carried out through the intervention/action research method with 11 users who were in open care and had low (or a propensity to low) self-esteem and who attended at least 6 ICT circles. Self-esteem and bond questionnaires proposed by Barreto have been used as instruments, whereas 12 ICT circles have been carried out as intervention throughout 3 months. In order to produce the empirical material, on its turn, the footage of all the circles has been used, as well as the field notebook and semi-structured interviews. This material has been analyzed accordingly to the content analysis technique. The results showed that the users showed an increase in their self-esteem and healthy bond scores, as well as a decrease in the fragile and risk ones. From a behavioral viewpoint, we have noticed that autonomy has been reestablished and bonds have been improved, in addition to an increase of empathic capacity and recognize in themselves their own potential. Conclusion: The ICT is an emancipatory practice and a potent tool for caring for mentally suffering people, inasmuch as it has shown to raise users’ self-esteem as well as to reestablish lost bonds and create solidarity networks so as to lead the those people to empowering by consequently recovering protagonism in their own lives.